A new Palaeocene crocodylian from southern Argentina sheds light on the early history of caimanines. Issue 1885 (22nd August 2018) - Bona, Paula; Ezcurra, Martín D.; Barrios, Francisco; Fernandez Blanco, María V.
Abstract : Caimanines are crocodylians currently restricted to South and Central America and the oldest members are from lower Palaeocene localities of the Salamanca Formation (Chubut Province, Argentina). We report here a new caimanine from this same unit represented by a skull roof and partial braincase. Its phylogenetic relationships were explored in a cladistic analysis using standard characters and a morphogeometric two-dimensional configuration of the skull roof. The phylogenetic results were used for an event-based supermodel quantitative palaeobiogeographic analysis. The new species is recovered as the most basal member of the South American caimanines, and the Cretaceous North American lineage ' Brachychampsa and related forms' as the most basal Caimaninae. The biogeographic results estimated north-central North America as the ancestral area of Caimaninae, showing that the Cretaceous and Palaeocene species of the group were more widespread than thought and became regionally extinct in North America around the Cretaceous–Palaeocene boundary. A dispersal event from north-central North America during the middle Late Cretaceous explains the arrival of the group to South America. The Palaeogene assemblage of Patagonian crocodylians is composed of three lineages of caimanines as a consequence of independent dispersal events that occurred between North and South America and within South America around the Cretaceous–Palaeogene boundary.